Mega LEO Satellite Constellations Networking: Challenges and Key Technologies - SUN Yaohua; FENG Xinao; PENG Mugen (天地一体化信息网络)
Owing to the advances in satellite manufacturing and rocket launch technology, the deployment of mega LEO constellations has become an important direction for the development of satellite Internet. Compared with traditional LEO constellations, new mega constellations, characterized by multi-orbit hybrid networking and stratified integration of satellites at different altitudes, exhibit new features such as a greater number of nodes and more dynamic topology. In light of these features, this paper first summarized the challenges of mega LEO constellations networking from five aspects: constellation design, protocol integration, topology representation, routing algorithms, and network simulation. It then introduced the key technologies for mega constellation networking, included network architecture, protocol design, network addressing, inter-satellite link establishment, and fault recovery, and provided outlooks on their development directions, aimed to offer references for the construction of Chinese satellite Internet.